Primary sternal osteomyelitis mimicking a neoplastic growth - Vinod, Nagadarshini Ramagiri; Tahir, Hassan; Ahmed, Arslan (International Journal of Research in Medical Sciences, 2017)
Chronic osteomyelitis usually present as bony growth but it can rarely present as a soft tissue growth mimicking neoplasm and is usually diagnosed by the combination of radiology and microbiology. This is a case report of an adult male who had chronic osteomyelitis mimicking a neoplastic growth of soft tissue. CT scan showed soft tissue mass mimicking a soft tissue tumor but microbiology test and MRI confirmed the diagnosis of chronic osteomyelitis.